TINDAKAN KOLEKTIF DAN IDENTITAS (Studi Fenomenologis Korban Lumpur Lapindo di Porong Sidoarjo) - Sukamto, Sukamto (Jurnal Sejarah dan Budaya, 2010)
Abstract: Lapindo Mud Phenomenon in Porong, Sidoarjo was not local social problems but widespread into international problem. This problems encoutered three power there are State, Corporate and Civil Society. Phenomenology, studies about life experience organized as conflict, negotiation and identity production on the society life world. Mentioned sloganâ Back to thing themselvesâ have done with Vokasio and Reduksio from the victim of Lapindo Mud. Negotiation classified into several type such as discussion, dialog, debate, demonstration, sending a letter to the corporate, fibbing, boycott, blocade, visiting upon DPRD until President. The populace considering state action to solve this problems more taken side into corporate than Lapondo Mud victims.